Kombinasi Aroma Terapi Lemon Dan Musik Rindik Untuk Mual Muntah Pada Ibu Hamil Trimester I - Rizky Meilani, Vika; Herliawati, Putu Arik; Dewi, Anak Agung Santi; Praminingrum, I Gusti Ayu Raras (JURNAL KEBIDANAN AKADEMI KEBIDANAN BUDI MULIA PALEMBANG, 2025)
Nausea and vomiting are common complaints in the first trimester of pregnancy due to increased levels of human chorionic gonadotropin (HCG) and progesterone. Complementary non-pharmacological treatments, such as aromatherapy and music, can help prevent the side effects of medications that can affect fetal growth and development. The objective was to determine the effectiveness of a combination of lemon aromatherapy and Rindik music for nausea and vomiting in first-trimester pregnant women at the Ni Putu Sri Sumartini TPMB. This study used a pre-experimental one-group pretest-posttest design. The study population was primiparous postpartum women. Primary data collection used the PUQE-24 questionnaire. The study period was March-April 2025. The results of the research were conducted using a computer application. Univariate data analysis and statistical analysis were performed with a significance level of p<0.05. The results of the univariate analysis showed that 19 pregnant women (63%) were aged 20-35 years, 7 respondents (23.3%) were aged <20 years, and 4 respondents (13.3%) were aged >35 years. Education level: 20 respondents were tertiary, 6 respondents (20%), and 4 respondents (13.3%). Parity: 19 respondents were primiparous (63.3%), and 11 respondents were multiparous (36.6%). The Shapiro-Wilk test for data normality was used. Data were analyzed using the Parried t-test. The analysis yielded a mean of 3.1 with a standard deviation of 1.592 and a p-value of 0.000. Because the p value <0.05 indicates that there is an effectiveness of the combination of lemon aromatherapy and rindik music for nausea and vomiting in pregnant women at TPMB Ni Putu Sri Sumartin. Breastfeeding in Postpartum Mothers at TPMB. It is hoped that health workers will always recommend the combination of lemon aromatherapy and rindik music as an alternative therapy to reduce nausea and vomiting.